Astilbin Inhibits Proliferation of Rat Aortic Smooth Muscle Cells Induced by Angiotensin Ⅱ and Down-regulates Expression of Protooncogene - 李平 高思海 揭伟 敖启林 黄亚非 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
This study examined the effect of astilbin on the proliferation of rat aortic smooth muscle cells (RASMCs) induced by angiotensin Ⅱ (AngⅡ) and explored the possible mechanisms. Cell proliferation model of RASMCs was induced by treatmente with AngⅡ. Cells were randomly di-vided to 8 groups. Normally cultured VSMCs serves as blank control group; in AngⅡ model group, cells were treated with AngⅡ at 10-7 mol/L; in three astilbin groups, cells were treated with 10, 15, 30 mg/L of astilbin; in three AngⅡ+astilbin groups, cells were treated with AngⅡ (at 10-7 mol/L) and astilbin at 10, 15, 30 mg/L. Cell proliferation ability was detected by MTT method and the cell cycles and proliferation index were flow cytometrically determined. The expression of c-myc mRNA was assessed by using reverse transcription polymerase chain reaction (RT-PCR), and the expression of NF-κB in RASMCs was immunocytochemically observed. Our results showed that MTT metabo-lism in RASMCs in the basic and AngII stimulated situation was inhibited by astilbin, and the cells numbers of G0/G1 phase were increased and that of G2/S phase were decreased markedly. Not only highly expression of c-myc gene stimulated by AngⅡ could be inhibited by Astilbin significantly, but also the expression of NF-κB protein can be down regulated by Astilbin. We are led to conclude that astilbin astilbin can inhibit the AngⅡ-mediated proliferation of RASMCs by blocking the tran-sition of RASMCs from G0/G1 phase to S phase and by down-regulating the expression of NF-κB, c-myc gene.